Two new hybrids of the genus Diplazium (Athyriaceae) from Japan - Hori, Kiyotaka (PhytoKeys, 2021)
In this study, we describe the ferns Diplazium × kanayamaense hyb. nov. and D. × tsukushiense hyb. nov. and further compare them to parental species D. chinense, D. deciduum and D. fauriei in terms of morphological characteristics, plastids and nuclear DNA markers. These new hybrids have been determined to be endemic to western Japan. The International Union for Conservation of Nature and Natural Resources status was evaluated for D. × kanayamaense as endangered (EN) and D. × tsukushiense as critically endangered (CR).